2009
DOI: 10.2147/ijn.s6630
|View full text |Cite
|
Sign up to set email alerts
|

Binding fullerenol C60(OH)24 to dsDNA

Abstract: Abstract:The first C 60 (OH) 24 -DNA complex and its fluorescence enhancement is reported. The enhanced fluorescence intensity of fullerenol C 60 (OH) 24 is in proportion to the concentration of DNA in the range of 1 × 10 -9 to 8 × 10 -5 molL -1 and the detection limit was 1.3 ng mL -1 . Fullerenol C 60 (OH) 24 binds significantly to the phosphate backbone of native dsDNA and to base-pairs within the major groove of sodium salt of dsDNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The Gd 3d spectrum of Gd@C 82 (OH) 22 showed the presence of a peak at 1188.1 eV assigned to the Gd atoms enclosed in the C 82 cage, confirming that the fullerene core remained intact during hydroxylation. The presence of hydroxygroups on the Gd@C 82 surface was also confirmed by the O 1s and C1s regions of the corresponding spectra (Figure S4), where peaks attributed to C–O bonds were observed at 285.6 and 532.7 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The Gd 3d spectrum of Gd@C 82 (OH) 22 showed the presence of a peak at 1188.1 eV assigned to the Gd atoms enclosed in the C 82 cage, confirming that the fullerene core remained intact during hydroxylation. The presence of hydroxygroups on the Gd@C 82 surface was also confirmed by the O 1s and C1s regions of the corresponding spectra (Figure S4), where peaks attributed to C–O bonds were observed at 285.6 and 532.7 eV, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Positive values of Δ H and Δ S are typical of hydrophobic interactions; therefore, it can be assumed that the formation of C 60 (OH) 24 complexes with DNA occurs due to the fullerene core. In ref , the authors showed that fullerenol C 60 (OH) 24 interacts with the phosphate backbone of the outer side of the native DNA double helix, as well as with pairs of nitrogenous bases inside the major groove of DNA. Comparison of K b shows that the values obtained in ref exceed the K b values obtained in this study by one to two orders of magnitude.…”
Section: Resultsmentioning
confidence: 99%
“…In ref , the authors showed that fullerenol C 60 (OH) 24 interacts with the phosphate backbone of the outer side of the native DNA double helix, as well as with pairs of nitrogenous bases inside the major groove of DNA. Comparison of K b shows that the values obtained in ref exceed the K b values obtained in this study by one to two orders of magnitude. This fact is due to the different temperature ranges in which the binding study was carried out, as well as due to the fact that different methods were used to obtain fullerenols and, as a consequence, the synthesized adducts had different compositions.…”
Section: Resultsmentioning
confidence: 99%
“…The high purity C 60 (OH) 24 sample was prepared as previously described [14–15] (see Supporting Information File 1). Freshly produced ultrapure water (TKA Lab TowerEDI 0.067–0.080 µS/cm) was used for sample preparation and as the mobile phase.…”
Section: Methodsmentioning
confidence: 99%
“…However, to the best of our knowledge, except for the compositionally and structurally well characterized C 60 (OH) 24 , prepared by alkaline hydrolysis of C 60 Br 24 [14–15], most of these fullerenols are not pure C 60 (OH) x , but a complex mixture of products with an average composition of C 60 (OH) x–y , C 60 O x (OH) y [1619] or C 60 (OH) x (ONa) y [20]. …”
Section: Introductionmentioning
confidence: 99%